Da “cor de pele” as cores de pele: a diversidade em foco nas escolas de educação infantil de Santa Maria-RS - Quadros, Taiana Flores de (2023)
This thesis was developed from the Doctorate course of the Postgraduate Program in education at the Federal University of Santa Maria, in the research line LP2 - “Educational public policies, educational practices and their interfaces”. The research problem is: To what extent does the construction of identity and racial recognition and belonging permeate children's interactions and what relationships can be established with the pedagogical practices of teachers in Early Childhood Education? The general objective was: to identify and analyze aspects related to the construction of identity and ethnic-racial recognition and belonging that permeate children's interactions, seeking to establish relationships with the pedagogical practices of teachers in Early Childhood Education. The study falls within the scope of qualitative research, which seeks to understand phenomena in their natural context without manipulating variables. To do this, it uses the technique of ethnography, originating in Anthropology, which focuses on understanding the meanings attributed to actions and events by people or groups studied. The research was carried out with the participation of 18 children between 4 and 5 years old from a public Early Childhood Education institution in the city of Santa Maria/RS, between August and September 2023. The following methodological instruments were used: observation, intervention, records written in the field diary, as well as photographic records. The theoretical framework was based on three distinct approaches that together help to understand how ethnic-racial identification, the meaning of experiences and the role of children in society are interconnected and influence the theme of this research: Theories about ethnic-racial identification; socio-historical approach to Psychology, focusing on the categories "sense" and "meaning" and the conception of the Sociology of Childhood, which sees the child as a legitimate social actor with rights. The results show that children do not use ethnic-racial categories, they seek to identify and name the skin color of other children. It was evident that the choices of teaching materials can impact children's perception of identity from childhood. Literature presents itself as a tool for promoting identification, representation, cultural diversity, combating stereotypes, awareness about history, anti-racist education, empowerment and empathy. Based on the research results, I defend the thesis that it is of fundamental importance to recognize racism as an existing problem in society and, consequently, in schools. There is a need for schools to adopt an anti-racist approach, which promotes the appreciation of ethnicracial diversity and mutual respect among students. Furthermore, there is a need to train teachers to deal with issues related to racism and discrimination. The effective implementation of Law 10.639/03 goes beyond the inclusion of curricular content; it requires a profound change in the mindset and attitude of educators. Teachers must be committed to promoting racial equality and deconstructing stereotypes and prejudices.